1998
DOI: 10.2337/diabetes.47.12.1824
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of amino acid exchange and protein dynamics across splanchnic and skeletal muscle beds by insulin in healthy human subjects.

Abstract: To define the mechanism of insulin's anticatabolic action, the effects of three different dosages of insulin (0.25, 0.5, and 1.0 mU x kg(-1) x min(-1)) versus saline on protein dynamics across splanchnic and skeletal muscle (leg) beds were determined using stable isotopes of phenylalanine, tyrosine, and leucine in 24 healthy subjects. After an overnight fast, protein breakdown in muscle exceeded protein synthesis, causing a net release of amino acids from muscle bed, while in the splanchnic bed protein synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(123 citation statements)
references
References 0 publications
3
118
1
1
Order By: Relevance
“…The increased circulating insulin levels on 11 days of insulin treatment substantially reduced fasting glucose levels but had little impact on circulating amino acid concentrations and amino acid kinetics, reflecting protein turnover. Previous studies in nondiabetic people demonstrated that leucine carbon flux declined progressively in a dose-dependent manner on intravenous insulin infusion (31,49,50). However, these dose-dependent effects clearly showed that the near-maximal insulin effect was achieved when insulin was infused at a dose of 1 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 (31).…”
Section: Discussionmentioning
confidence: 78%
“…The increased circulating insulin levels on 11 days of insulin treatment substantially reduced fasting glucose levels but had little impact on circulating amino acid concentrations and amino acid kinetics, reflecting protein turnover. Previous studies in nondiabetic people demonstrated that leucine carbon flux declined progressively in a dose-dependent manner on intravenous insulin infusion (31,49,50). However, these dose-dependent effects clearly showed that the near-maximal insulin effect was achieved when insulin was infused at a dose of 1 mU ⅐ kg Ϫ1 ⅐ min Ϫ1 (31).…”
Section: Discussionmentioning
confidence: 78%
“…It is well recognized that increased availability of mitochondrial protein is associated with increased respiration (13,35). By increasing mitochondrial protein synthesis and possibly decreasing protein breakdown (36)(37)(38), insulin may increase mitochondrial protein content and could thus enhance mitochondrial respiration. Previous studies have meticulously revealed many of the subcellular mechanisms by which insulin stimulates muscle protein synthesis, most involving the up-regulation of translational steps (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia, as was present in our subjects with NASH, has been shown to differentially inhibit hepatic protein synthesis and degradation. [54][55][56] Although our primary goal was to determine the relative expression of genes involved in the mitochondrial function and glucose and lipid metabolism, the finding that several mediators of inflammation were expressed differentially also merits consideration. Hepatocyte-derived fibrinogen-related protein 1, complement compo-nent C3, and ␣-1 antitrypsin, all acute phase reactants, also were relatively overexpressed in subjects with NASH.…”
Section: Discussionmentioning
confidence: 99%